Genres of Reading Comprehension Passages in Chinese Mainland National Matriculation English Test (NMET): A Systematic Analysis of the Last Twenty Years (2004–2023) - Dong Wang; Zhexi Ye (SAGE Open)
Reading comprehension constitutes an important part of the Chinese National Matriculation English Test (NMET) which influences English teaching practice greatly. Despite the focus of many studies on NMET reforms, content validity, and washback effects, there remains a notable gap in research regarding the genre of reading texts in NMET. Drawing on the systemic functional linguistics (SFL) notion of micro-genres, this study analyzes the micro-genres of the reading passages ( n = 240) tested in Chinese NMET from 2004 to 2023. It reveals that these passages cover a wide range of micro-genres. However, the genre distribution is imbalanced with stories leading a dominating role while arguments, text responses and compositional reports get less attention. To improve reading comprehension tasks designed in NMET, the study calls for a more balanced distribution and diverse genres in test propositions and sheds light on the teaching practices reforms in EFL classes.